The Effect of Financial Literacy, Income, and Financial Behaviour on Gen-Z Investment Decisions in Bekasi Regency - Suhendar, Diki; Fahamsyah, Mohammad Hatta (Jurnal Manajemen Bisnis, 2024)
Investment is now a hot topic among young people, especially among Gen-Z. This research focuses on the interest of Generation Z in Bekasi Regency towards investment and their choice of investment instruments. Through a qualitative approach using questionnaires and literature studies, it was found that Gen-Z's interest in investment is very high. The research conducted on 209 Gen-Z in Bekasi Regency aims to examine the impact of financial literacy, income, and financial behaviour on their interest in investing, as well as the investment instruments they choose. Gold emerged as their favourite investment instrument because it is easy to use and has a low risk of loss. The findings show the great potential of Gen-Z in managing finance and investment in Bekasi Regency.